Evaluation of Periodontal Ligament Cell Viability in Three Different Storage Media: An in Vitro Study - Meenakshi Sharma; Sanjay Sharma; Y. G. Reddy; Rakesh Mittal; Vishal Agarwal; Chanchal Singh; Amandeep Singh (Tehran University of Medical Sciences, 2016)
Objectives: This study was undertaken to evaluate the viability of periodontal ligament (PDL) cells of avulsed teeth in three different storage media. Materials and Methods: Forty-five premolars extracted for orthodontic therapeutic purposes were randomly and equally divided into three groups based on storage media used [Group I: milk (control); Group II: aloe vera (experimental); Group III: egg white (experimental)]. Following extractions, the teeth were placed in one of the three different storage media for 30 minutes, following which the scrapings of the PDL from these teeth were collected in Falcon tubes containing collagenase enzyme in 2.5 mL of phosphate buffered saline. The tubes were subsequently incubated for 30 minutes and centrifuged for five minutes at 800 rpm. The obtained PDL cells were stained with Trypan Blue and were observed under optical microscope. The percentage of viable cells was calculated. Results: Aloe vera showed the highest percentage of viable cells (114.3±8.0), followed by egg white (100.9±6.3) and milk (101.1±7.3). Conclusion: Within the limitations of this study, it appears that aloe vera maintains PDL cell viability better than egg white or milk.